How gun control policies evolve: Gun culture, 'gunscapes' and political contingency in post-Soviet Georgia. (November 2020) - Light, Matthew; Slonimerov, Eugene
We analyse the influence of gun culture and exogenous political events on gun regulation in post-Soviet Georgia. While neighbouring states retain restrictive Soviet-era gun laws, in Georgia, state failure, armed conflict and proliferation of weapons during the 1990s all impelled recent governments towards moderate gun policies, including liberal rules on handgun ownership, strict rules on gun carriage and a national gun registry. We conceptualize gun policy as the product of relatively durable institutional legacies and underlying social attitudes—in this case, a distinctive post-communist 'gunscape'—which constrain future policy development; and specific political conjunctures, which provide opportunities for limited policy experimentation. While Georgian gun owners desire weapons for self-defence, sport and the affirmation of masculinity, they do not seek to defy the state or replace its role in collective security, leading to a moderate 'harm reduction' approach to regulation that may be applicable in other post-conflict societies.